In situ Sensing of Single Binding Events by Localized Surface Plasmon Resonance - Sannomiya, Takumi; Hafner, Christian; Voros, Janos (Nano letters, 2008)
Single binding events of nanoparticle-labeled DNA strands were detected as stepwise peak shifts in localized surface plasmon resonance by single particle measurement. We confirmed the number of binding events by observing label particles by scanning electron microscopy. Our simulation based on a multiple multipole program showed that the peak shift is dependent on interparticle gap size and binding position. The experimental peak shift distribution was also reproduced by simulation.